The Secret of the Exponential Function in View of Mankind - Doepp, Manfred (European Journal of Applied Sciences, 2023)
We have become accustomed to the fact that the economy in the individual countries and in the world needs continuous growth rates in order to ensure our prosperity. This is understandable, but mathematically wrong. Because regular quantitative growth means that exponential growth is created, which must lead to catastrophe. The exponential function implies that the average quantity must remain in a dynamic and sustainable equilibrium if disaster is not to occur. Not affected by this are changes in quality, as they occur in nature. If humanity does not change its purely quantitative objectives of production and gross social products, it can be predicted that it will not be able to persist.